Risk factors and characteristics of new-onset coronary heart disease in adults with physical disabilities: A retrospective cohort study. Issue 3 (March 2023) - Wu, Jing; Huang, Lan; Wu, Airong; Xu, Jianlei; Wu, Zhenghong; Le, Meihua; Jiang, Chenghua; Wu, Hengjing
Abstract: Objectives: There is limited information about coronary heart disease (CHD) in adults with physical disabilities. This study was performed to assess the incidence and predictors of the new development of CHD in adults with physical disabilities. Methods: A retrospective cohort study was performed on 3902 physically disabled people in Shanghai, China. Baseline information was collected in January 2012, and participants were followed-up with for 7.5 years for CHD events. Risk factors for demographic characteristics, disease history, electrocardiography, and blood biochemical indicators were evaluated using a Cox proportional hazard model. Subgroup analyzes were performed according to gender and level of physical disability. Results: Out of the total 3902 adults with physical disabilities (average age 55.9 ± 8.5 years), 468 (12.0%) developed CHD, during a median follow-up period of 7 years. Independent predictors of CHD included the following: age (HR = 1.411, 95% CI = 1.255–1.587, p ＜0.001), gender (HR = 0.773, 95% CI = 0.637–0.940, p  = 0.010), abnormal electrocardiogram(HR = 1.396, 95% CI = 1.088–1.792, p  = 0.009), hypertension (HR = 1.657, 95% CI = 1.369–2.006, p ＜0.001), diabetes (HR = 1.649, 95% CI = 1.307–2.081, p ＜0.001), serum uric acid (HR = 1.001, 95% CI = 1.000–1.002, p  = 0.046), and total cholesterol (HR = 1.416, 95% CI = 1.054–1.902, p  = 0.021). In addition to the risk factors of the total population with physical disability, triglyceride was also a significant risk factor for CHD in the subgroup with women and mild disability. Conclusions: During a 7.5 years period, the CHD incidence rate among physically disabled people was 12.0%. We identified the role of CHD risk factors such as age, gender, hypertension, diabetes, serum uric acid, total cholesterol, and abnormal electrocardiogram.